Análise tomográfica 3D da via áerea faríngea na Síndrome de Treacher Collins e sua relação com o padrão esquelético - Ribeiro, Alexandre de Almeida (2019)
Introduction: Treacher Collins syndrome (TCS) is a rare (1:50.000 live births) and severe anomaly of craniofacial development. It arises mainly from mutations in TCOF1 gene mapped at chromosome 5 and affects the development of first and second branchial arches. Maxillomandibular hypoplasia is among the main craniofacial characteristics. Objectives: This study aimed at investigating the skeletal craniofacial and pharyngeal morphologies of individuals with TCS, by means of cone beam computed tomography (CBCT) and to compare these data with those from a control population. Methods: CBCT scans of 26 individuals had the pharyngeal volume (V) and minimal cross-sectional area (mCSA) evaluated. The study group (TCS) was composed by CBCT scans of individuals (n=13) with TCS (7 males and 6 females; 20.2±4.7y). Control group (CG) was composed by CBCT scans of non-syndromic subjects (n=13) with the same type of skeletal pattern (2 males and 11 females; 26.6 ± 5.4y). Cephalometric data of maxillomandibular position, maxillomandibular dimensions and growth pattern were assessed. Statistics included Student t test and Pearson Correlation Coefficient (p 0.05). Results: Pharyngeal V and mCSA of TCS were smaller, although not significantly. Minimum CSA was located at the oropharyngeal level on the great majority of the cases. The jaws of TCS were significantly retropositioned and reduced, especially the mandible. It was observed a hiperdivergent growth pattern in TCS subjects. Conclusion: TCS is a skeletal class II high angle craniofacial malformation with reduced pharyngeal dimensions when compared with a control group. The micro and retrognathia seem to affect negatively the pharyngeal dimension of TCS population